KELAYAKAN FINANSIAL DAN PEMBIAYAAN BATIK BERBASIS PEWARNA ALAMI STRATEGI PENGUATAN DAYA SAING PARIWISATA BERKELANJUTAN DI SEMARANG - Suyati, Sri; Aminah, Siti; Parju, Parju; Nurchayati, Nurchayati; Suparmi, Suparmi; Prasetyo, Heru Eko; Amzar, Amzar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Batik is an Indonesian cultural heritage recognized by UNESCO as Intangible Cultural Heritage since 2009. In the midst of modern industrial development, conventional batik production faces serious challenges related to environmental impacts from synthetic chemical dye use. This community service program aims to develop environmentally friendly batik by integrating proper financial analysis and financing strategies for SME craftspeople, while linking it to the sustainable tourism ecosystem. Financial studies include investment feasibility analysis (Net Present Value/NPV, Internal Rate of Return/IRR, and Payback Period), social capital-based financing structures, and potential access to green financing from financial institutions. Activities were carried out at Tapak Dara Village, Meteseh Sub-district, Tembalang District, Semarang City in February 2026, involving at least 30 batik artisans. Expected outcomes include improved financial literacy of craftspeople, development of bankable business models, at least 30% income growth, and the creation of high-value creative ecotourism packages. This program contributes to achieving the Sustainable Development Goals (SDGs), particularly goals 8 (Decent Work and Economic Growth) and 12 (Responsible Consumption and Production).